Conservative Management of an Iatrogenic Esophageal Tear in Kenya. (14th July 2015) - Waweru, Peter; Mwaniki, David
Abstract : Since its description over 250 years ago, diagnosis of esophageal perforation remains challenging, its management controversial, and its mortality high. This rare, devastating, mostly iatrogenic, condition can quickly lead to severe complications and death due to an overwhelming inflammatory response to gastric contents in the mediastinum. Diagnosis is made with the help of esophagograms and although such tears have traditionally been managed via aggressive surgical approach, recent reports emphasize a shift in favor of nonoperative care which unfortunately remains controversial. We here present a case of an iatrogenic esophageal tear resulting from a routine esophagoscopy in a 50-year-old lady presenting with dysphagia. The esophageal tear, almost missed, was eventually successfully managed conservatively, thanks to a relatively early diagnosis.